Glycosyl Fluorides as Intermediates in BF3·OEt2‐Promoted Glycosylation with Trichloroacetimidates. Issue 9 (8th March 2017) - Nielsen, Michael M.; Stougaard, Bolette A.; Bols, Mikael; Glibstrup, Emil; Pedersen, Christian M.
Abstract : Glycosyl fluorides have been found to be important intermediates in glycosylations with trichloroacetimidate donors and BF3 · OEt2 activation (0.2–1 equiv.). Low‐temperature NMR spectroscopy experiments revealed that the α‐trichloroacetimidate was transformed into the glycosyl fluoride with inversion of stereochemistry, whereas the β anomer was not. A concerted mechanism was suggested for the stereospecific formation of glycosyl fluorides, which is not accounted for in the classic mechanism. Abstract : Glycosyl fluorides are important intermediates in glycosylations with trichloroacetimidate (TCA) donors and BF3 · OEt2 activation. Low‐temperature NMR spectroscopy experiments reveal that the α‐TCA is transformed into the glycosyl fluoride with inversion of stereochemistry, whereas the β anomer is not.